2006
DOI: 10.1007/s00425-006-0292-2
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear-encoded ClpP subunit of the chloroplast ATP-dependent Clp protease is essential for early development in Arabidopsis thaliana

Abstract: ClpP4 is a nuclear-encoded plastid protein that functions as a proteolytic subunit of the ATP-dependent Clp protease of higher plants. Given the lack of viable clpP4 knockout mutants, antisense clpP4 repression lines were prepared to study the functional importance of ClpP4 in Arabidopsis thaliana. Screening of transformants revealed viable lines with up to 90% loss of wild type levels of ClpP4 protein, while those with> 90% were severely bleached and strongly retarded in vegetative growth, failing to reach re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 42 publications
5
52
0
Order By: Relevance
“…Interestingly, antisense inhibition of clpP6 produces a similar but less severe chlorotic phenotype to the antisense repression of clpP4, despite both sets of transgenic lines having similar levels of protein repression (i.e., 80 to 90%). Despite this difference in severity, the chlorotic phenotype of the clpP4 antisense lines lessened upon maturation, as did that in the clpP6 antisense lines (Zheng et al, 2006), consistent with the fact that both ClpP paralogs function within the same proteolytic core (Peltier et al, 2001(Peltier et al, , 2004.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Interestingly, antisense inhibition of clpP6 produces a similar but less severe chlorotic phenotype to the antisense repression of clpP4, despite both sets of transgenic lines having similar levels of protein repression (i.e., 80 to 90%). Despite this difference in severity, the chlorotic phenotype of the clpP4 antisense lines lessened upon maturation, as did that in the clpP6 antisense lines (Zheng et al, 2006), consistent with the fact that both ClpP paralogs function within the same proteolytic core (Peltier et al, 2001(Peltier et al, , 2004.…”
Section: Discussionsupporting
confidence: 58%
“…Despite this, the ClpP4 self-complex could not associate with the ClpP1/R1-4 subcomplex to form an intact Clp proteolytic core and thus could not compensate for the loss of ClpP6. In an earlier study, antisense repression of clpP4 was also shown to cause a downregulation of associated ClpP paralogs but no significant change in the subunits of the ClpP1/R1-4 subcomplex (Zheng et al, 2006). In this case, both ClpP3 and ClpP5 are downregulated to the same extent as ClpP4 (;80%), whereas ClpP6 is downregulated to a lesser extent (;30%) (Zheng et al, 2006).…”
Section: Discussionmentioning
confidence: 66%
“…Rapid suppression of Rubisco activase and chloroplastic Clp protease, which was also observed under natural salt stress in P. euphratica , may be required for the down-regulation of photosynthetic CO 2 assimilation and the stress adaptation of the photosynthetic apparatus, respectively (Zheng et al, 2006;Wang et al, 2007;Stanne et al, 2009). Decreased PSII yield occurred only after the leaves started to accumulate sodium and was probably caused by suppression of the biosynthesis of PSII D1 protein (psbA), Qa protein, and Rubisco large subunit.…”
Section: Stress Acclimation Involves a Redirection Of Protein Metabolmentioning
confidence: 90%
“…Amino acid identities between the processed ClpP/R subunits range from 24 to 48% (Kim et al, 2009). Genetic and phenotypic analyses of various ClpP/R mutants in plants showed that the proteolytic and nonproteolytic subunits have differential functional contributions and all of them, except ClpR1, are essential for embryo or seedling development (Rudella et al, 2006;Sjö gren et al, 2006;Zheng et al, 2006;Koussevitzky et al, 2007;Kim et al, 2009;Zybailov et al, 2009b) (reviewed in Kato and Sakamoto, 2010;Olinares et al, 2011).…”
Section: Introductionmentioning
confidence: 99%